School dropout in Integrated High School of the Federal Education Network in the capitals of the North Region, Brazil (2014-2018) (Research, Society and Development, 2020)
Secondary education is the final stage for the formation of an individual at the basic level of education. The integrated modality is characterized by the union between High School and Professional Education in the same enrollment. School dropout occurs when the student does not attend school, which characterizes the abandonment of studies. The aim of this paper is to analyze data on school dropout in integrated high school from the Federal Education Network in the capitals of the Northern Region of Brazil, in the period from 2014 to 2018. For this purpose, a bibliographical and documentary search was carried out. As for the approach, this study involves mixed methods (quanti-qualitative). Quantitative data were accessed in the database of the National Institute of Educational Studies and Research Anísio (INEP). After accessing this information, we obtained the following results, in which the North Region presented a difference for less, in the number of students per class, when comparing the last and the first year of High School, and that among all the capitals of the Region Norte, the city of Rio Branco in Acre, showed the greatest decrease in the number of students per class. We realize that public policies to combat and effectively diagnose evasion are scarce. Thus, it is important to identify the causes of evasion, as it is something complex, and it has several motivations, needing to be studied continuously. Thus making possible an attempt to minimize the problem of evasion, which plagues Brazilian education.